2011
DOI: 10.1103/physreva.83.053617
|View full text |Cite
|
Sign up to set email alerts
|

Controlling directed transport of matter-wave solitons using the ratchet effect

Abstract: We demonstrate that directed transport of bright solitons formed in a quasi-one-dimensional Bose-Einstein condensate can be reliably controlled by tailoring a weak optical lattice potential, biharmonic in both space and time, in accordance with the degree of symmetry breaking mechanism. By considering the regime where matter-wave solitons are narrow compared to the lattice period, (i) we propose an analytical estimate for the dependence of the directed soliton current on the biharmonic potential parameters tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 38 publications
0
29
1
Order By: Relevance
“…V). This is interesting because there are only a few reports on ratchets with nontopological solitons [12][13][14]; most of the literature concerns ratchets with topological solitons, e.g., [15][16][17][18][19]. In Ref.…”
Section: U + δU = R[u(xt); Xt]mentioning
confidence: 99%
“…V). This is interesting because there are only a few reports on ratchets with nontopological solitons [12][13][14]; most of the literature concerns ratchets with topological solitons, e.g., [15][16][17][18][19]. In Ref.…”
Section: U + δU = R[u(xt); Xt]mentioning
confidence: 99%
“…This universal waveform is a direct consequence of the degree of symmetry breaking (DSB) mechanism: It is possible to consider a quantitative measure of the DSB on which the strength of directed transport by symmetry breaking must depend. Such a theory of the ratchet universality has been applied to predict successfully the behavior of two kinds of soliton ratchets [5,6]. The theory demonstrated in our original article [2] uses, among other theoretical ideas, ratchet universality to explain the interplay between thermal noise and symmetry breaking in the ratchet transport of Eq.…”
mentioning
confidence: 99%
“…Relatively recently ratchet dynamics has been shown to exist for quasiparticles, such as solitons and large polarons [6][7][8][9][20][21][22][23]. In particular, it has been demonstrated that directed transport of bright solitons formed in a quasi-one-dimensional nondissipative Bose-Einstein condensate can be induced by a weak spatiotemporal biharmonic optical lattice potential [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%